2015
DOI: 10.1590/0100-83582015000200022
|View full text |Cite
|
Sign up to set email alerts
|

Carryover of Imazethapyr + Imazapic on Ryegrass and Non-tolerant Rice as Affected by Thickness of Soil Profile

Abstract: -Herbicides used in Clearfield ® rice system may persist in the environment, damaging non-tolerant crops sown in succession and/or rotation. These damages vary according to soil characteristics, climate and soil management. The thickness of the soil profile may affect carryover effect; deeper soils may allow these molecules to leach, reaching areas below the roots absorption zone. The aim of this study was to evaluate the effect of the thickness of soil profile in the carryover of imazethapyr + imazapic on rye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The subject discussed in the present experimentimpact of ALS inhibitor herbicides associated to Clearfield ® technology on succeeding crops, is studied by some researchers in slightly different edapho-climatic conditions. In a study similar to the present one, but installed under controlled environment (lysimeters), Bundt et al (2015) reported no visual symptoms of intoxication to ryegrass, but some reduction in dry mass when this species was planted 128 DAA of Kifix ® ; the same authors reported damages to rice planted on the succeeding summer (1 year after application) of about 70% in rice dry mass, compared to the control treatment with no application.…”
Section: Soybeansupporting
confidence: 77%
“…The subject discussed in the present experimentimpact of ALS inhibitor herbicides associated to Clearfield ® technology on succeeding crops, is studied by some researchers in slightly different edapho-climatic conditions. In a study similar to the present one, but installed under controlled environment (lysimeters), Bundt et al (2015) reported no visual symptoms of intoxication to ryegrass, but some reduction in dry mass when this species was planted 128 DAA of Kifix ® ; the same authors reported damages to rice planted on the succeeding summer (1 year after application) of about 70% in rice dry mass, compared to the control treatment with no application.…”
Section: Soybeansupporting
confidence: 77%
“…Although not causing severe damage to the two tolerant rice varieties studied, it is important to emphasize that imidazolinone herbicides have high persistence in the soil, being that their sorption is higher in soils with low pH and high organic matter (Kraemer et al, 2009a). In this way, the utilization of high rates may hamper the growing of crops in succession and rotation with Clearfield ® rice as ryegrass in the off-season and imidazolinones non-tolerant rice in the next growing season (Kraemer et al, 2009b;Bundt et al, 2015). Furthermore, this practice can lead to increased selection pressure, increasing the possibility of emergence of new resistant weeds.…”
Section: Resultsmentioning
confidence: 99%
“…Pinto et al (2009b) also emphasize that there is a linear reduction in the dry matter of this crop due to the increase of the residue of these herbicides, applied to the rice in the previous growing season. According to Bundt et al (2015), the seeding performed 128 days after application causes a reduction in the ryegrass dry matter. This finding corroborates with the present study, where the crop was planted 129 days after application.…”
Section: Experiments With Soil Moisture Above 70% Of Field Capacity Inmentioning
confidence: 99%